DESIGN AND VALIDATION OF A MODIFIED ODENTHAL INDEX-BASED ROLLOVER WARNING SYSTEM FOR COMMERCIAL VEHICLES - Zubir, A. R.; Harun, M. H.; Muhammad, A. A.; Ahmad, F.; Rahmat, M. S. (Journal of Engineering and Technology (JET), 2026)
Commercial vehicle accidents, particularly rollovers of lightweight trucks, are frequently reported in the mass media. Rollovers have a significantly higher fatality rate than other types of crashes, posing serious risks to both drivers and passengers. Multiple factors contribute to rollover incidents, resulting in severe injuries and fatalities. This study aims to develop a Rollover Warning Device (RWD) specifically designed for commercial vehicles that exhibit a greater center of gravity height-to-track width ratio. This system collects real-time vehicle motion data and assesses rollover risk through a rollover index (RI) algorithm based on the load transfer ratio (LTR) that is implemented in the rear-wheel drive (RWD) of the vehicle. MATLAB/Simulink is used to optimize the block model parameters and evaluate the rollover index by analyzing step-steering maneuvers at various speeds. To further validate the system, the enhanced Odenthal rollover index approach is integrated into the TruckSim driving simulator and MATLAB/Simulink software. Hardware-in-the-loop (HIL) simulation models the step-steering maneuvers under different speed and load conditions. The experimental results demonstrate that the modified Odenthal rollover index algorithm improves Time-to-Warn (TTW) by 12.5% compared to the original Odenthal index. Additionally, this approach ensures a suitable Time-to-Respond (TTR), allowing drivers to take corrective action effectively. By refining the early warning system, the enhanced Odenthal rollover index algorithm significantly reduces the likelihood of rollover incidents, thereby improving commercial vehicle safety.